Stakeholder perspectives to inform the implementation of a community health worker-delivered home management of hypertension intervention in Zimbabwe - Paddington Tinashe Mundagowa; Malvin Musariri; Pamela Magande; Tendai Hlabangana; Linda Jane Mukwambo; Pemberai Zambezi; Priscillah Muchemwa-Munasirei; Fadzai Mukora-Mutseyekwa (BMJ Open)
Objective Implementing evidence-based innovations often fails to translate into meaningful outcomes in practice due to dynamic real-world contextual factors. Identifying these influencing factors is pivotal to implementation success. This study aimed to determine the barriers and facilitators of implementing a community health worker (CHW)-delivered home management of hypertension (HoMHyper) intervention from a stakeholder’s perspective using the Consolidated Framework for Implementation Research (CFIR).Design Exploratory qualitative study.Setting Five primary healthcare facilities in Mutare City, Zimbabwe.Participants 25 CHWs, 10 health facility nurses and 3 Mutare City health administrators.Results Perceived barriers to implementation of the HoMHyper intervention were staff shortage, patient privacy and confidentiality, limited access to antihypertensive medication, CHW incentivisation and equipment shortage, as well as patient knowledge and beliefs about hypertension. The proposed intervention was superior to the current practice, easy to implement and adaptable in the local context. Perceived facilitating factors were commitment from health system leadership, CHW training and support, regular engagement between CHWs and health providers, community partnerships, and CHW self-efficacy and knowledge and skills.Conclusion Integrating CHWs into chronic disease management can potentially improve health service access in low-resource settings. Well-coordinated planning guided by implementation evidence frameworks such as the CFIR significantly enhances the identification of important barriers and facilitators to inform implementation.